2021
DOI: 10.16993/sjdr.772
|View full text |Cite
|
Sign up to set email alerts
|

A Right to be Included: The Best and Worst of Times for Learners with Disabilities

Abstract: This paper presents a critical analysis of the temporal politics of inclusive education. Drawing on the misalignment of universalist human rights discourse with the prevalence of materialist conceptualisations of disability, it instead advocates for a non-representative and temporal approach to inclusive practice. In four parts, it begins by presenting a temporal framework to the analysis of disability and inclusive education. Characterising the historical present as the best and worst of times for people with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As Shulman notes "the teacher must have at hand a veritable armamentarium of alternative forms of representation, some of which derive from research whereas others originate in the wisdom of practice" (1986, p. 9). Whilst experienced educators can draw on their history of having techniques to draw on and established relationships with their cohorts that can save time, in contrast, less inexperienced teachers often become quickly overwhelmed and reliant on policy positions and default responses (Whitburn & Thomas, 2021).…”
Section: Part 4: Discussion: Relationships Take Timementioning
confidence: 99%
“…As Shulman notes "the teacher must have at hand a veritable armamentarium of alternative forms of representation, some of which derive from research whereas others originate in the wisdom of practice" (1986, p. 9). Whilst experienced educators can draw on their history of having techniques to draw on and established relationships with their cohorts that can save time, in contrast, less inexperienced teachers often become quickly overwhelmed and reliant on policy positions and default responses (Whitburn & Thomas, 2021).…”
Section: Part 4: Discussion: Relationships Take Timementioning
confidence: 99%
“…Meanwhile, inclusion in a course is mobilised as either a demonstrated capacity for individuals to perform at a particular standard, or else a demonstrated ability to receive bolt-on support guaranteed to meet this standard as a stated minimum. Ignored are any number of considerations: the intermittency of some disabling conditions; the contingent corollaries of social disruptions; the asymmetry and non-normativity of time for people with disabilities (Whitburn & Thomas 2021); nor, most importantly, how education is yet to engage disability in a meaningful and inclusive way (Naraian 2021;Slee 2018).…”
Section: Challenging the Ableist Discourse Of Knowing Disability In I...mentioning
confidence: 99%
“…The Convention in the United Nations of 2006 made an international right to persons with disabilities (special abilities) and established it worldwide, the cause of this was the difference in school inclusion in many countries due to the conditions of the structure of the school system and the educational institution itself, despite being recognized as of primary need and primary attention worldwide [1], it is for this reason that thanks to globalization and digitization there is a more noticeable difference in cultures and traditions, Therefore, it is urgent to find new teaching and learning strategies that support multidimensional and ethnocultural diversity [2], affecting not only the lower levels of education, but also the university levels where there is a greater concentration and diversity of cultures that lead to discrimination and/or rejection despite the existence of a study where neither of these two factors is found, concentrating on factors such as religion, sex, age and political ideology [3]. Fundamental and international rights have a political commitment in the education sector to maintain equity and quality inclusion [4], based on the declaration of the International Convention where special abilities were conceptualized and reaching results such as inclusion in a legal and mandatory way for education [5], as also achieved that many countries develop programs with intellectual and multiple abilities to have specialized care, share moments of inclusion with the society in which they live and achieving positive results in their learning [6].…”
Section: Introductionmentioning
confidence: 99%